PENGARUH MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA GAMBAR BERSERI TERHADAP KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS VII SMP NEGERI 1 LENGAYANG - Hurul Aini, Tahlia; Hafrison, Mohamad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is a quantitative research with experimental method. The research design used is One Group Pretest and Posttest. The variables of this research are the skills of writing news texts before using the PjBL model assisted by serial image media and after using the PjBL model assisted by serial image media. The population in this study were all seventh grade students of SMP Negeri 1 Lengayang with a total of 304 students spread across eight classes. The sample of this study was 38 students taken using purposive sampling technique. The research instrument was a performance test. Data were analyzed using statistical tests. The results showed that there was a significant increase in students' writing skills after the application of the PjBL model assisted by serial image media.